2008
DOI: 10.4161/cc.7.6.5597
|View full text |Cite
|
Sign up to set email alerts
|

PolyHEMA spheroids are an inadequate model for the drug resistance of the intractable solid tumors

Abstract: Cancers arising in pancreas, lung, liver and stomach are difficult to treat successfully. Wanting to understand the basis for such intractability, we previously performed comparative analyses of publicly available gene expression data from tumor biopsies. Expression of many cell adhesion genes correlated significantly with intractability of cancers, our surrogate of intractability being the SEER five-year survivals of patients with disseminated tumors. To model resistance mediated by cell adhesion, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…On surfaces unsuitable for cell adhesion, cells aggregate into spheroids because they show only minimal adhesion to the substratum surface [16][17][18]. However, under such conditions, cells are unable to show anchorage-dependent growth [17,18]. Therefore, when a nonadhesive culture substratum is used, the size of multicellular spheroids is dependent on the number of seeded cells [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On surfaces unsuitable for cell adhesion, cells aggregate into spheroids because they show only minimal adhesion to the substratum surface [16][17][18]. However, under such conditions, cells are unable to show anchorage-dependent growth [17,18]. Therefore, when a nonadhesive culture substratum is used, the size of multicellular spheroids is dependent on the number of seeded cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…Two types of surface properties of the culture substratum are known to affect the development of cell spheroids, one being unfavorable and the other partially favorable for cell adhesion. On surfaces unsuitable for cell adhesion, cells aggregate into spheroids because they show only minimal adhesion to the substratum surface [16][17][18]. However, under such conditions, cells are unable to show anchorage-dependent growth [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…So, an effective and improved drug development, drug delivery and drug testing programme are the need of hour to make significant inroads in a fight against cancer. It is important to mention that Steadman et al raised concerns about the possibility that the chemoresistance mechanisms found in spheroids may differ from the resistance found in intractable solid tumors in patients [61]. If this is the case, drugs selected by this system will be ineffective in primary tumors.…”
Section: Lung Cancer -Strategies For Diagnosis and Treatmentmentioning
confidence: 99%
“…These findings suggest that MCS formation may be dependent on tumor cell adhesion molecules and culture conditions. In addition, different MCS formation techniques may lead to different MCS phenotypes with different gene expression patterns [44]. Thus, it is essential to carefully select the most appropriate method.…”
Section: Mcs Culture Models Of Prostate Cancer Cellsmentioning
confidence: 99%